Association of Socioeconomic Status With Ischemic Stroke Survival. Issue 12 (December 2019) - Vivanco-Hidalgo, Rosa Maria; Ribera, Aida; Abilleira, Sònia
Abstract : Background and Purpose—: The aim of the study was to determine the impact of individuals' socioeconomic status and their Primary Care Service Area Socioeconomic Index on survival after ischemic stroke. Methods—: We conducted a nationwide population-based cohort study in Catalonia, Spain. We included all patients with first ischemic stroke admitted to a public hospital between January 1, 2015, and December 31, 2016. We measured both individual socioeconomic status (categorized as exempts, <[Euro sign]18 000 [$US 20 468] income per year, and >[Euro sign]18 000 income per year) and Primary Care Service Area Socioeconomic Index (from 0 to 100 categorized in quartiles). We used mixed-effects logistic and survival models to estimate odds ratios and hazard ratios for the short- (30 days) and the long-term (3 years) all-cause case fatality rates by individuals' socioeconomic status groups. Results—: The cohort consisted of 16 344 ischemic stroke patients with 24 638 person-years of follow-up. We did not find an association between the lowest socioeconomic individual status and short-term survival (odds ratio, 1.03; 95% CI, 0.76–1.40), although we found it in patients with <[Euro sign]18 000 income/year (odds ratio, 1.26; 95% CI, 1.10–1.45). At long-term, after adjustment, we observed a gradient in mortality risk with decreasing individual socioeconomic status (hazard ratio, 1.52; 95% CI, 1.30–1.77). The Primary Care Service Area Socioeconomic Index had only an influence on short-term survival (odds ratio, 1.19; 95% CI, 1.03–1.37). Conclusions—: Individuals' socioeconomic status was associated with short- and long-term survival in patients with ischemic stroke. Conversely, Primary Care Service Area Socioeconomic Index measures had an influence only in short-term survival. A small fraction of this association is due to differences in comorbidity and cardiovascular risk factors. Interventions addressing both individuals' and primary care service socioeconomic aspects might eventually affect differently short- and long-term survival. Abstract : Supplemental Digital Content is available in the text.